Determinan Stunting pada Anak Usia 0-24 Bulan di Wilayah Kerja Puskesmas Indrajaya Kabupaten Pidie Tahun 2022 - Sri Muliasari; Ramadhaniah Ramadhaniah; Nopa Arlianti (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Stunting or short is a condition where children experience failure to grow and develop so that children have a shorter height than the standard age. The prevalence of stunting at the Indrajaya Public Health Center was 240 cases. The purpose of this study was to find out what factors were associated with the incidence of stunting in children aged 0-24 months in the Indrajaya Public Health Center, Pidie Regency in 2022. This type of research was observational analytic with a case control approach. The population is all mothers of infants aged 0-24 months as many as 70 mothers of infants in the Caleue settlement. Sampling in this study was conducted in the Caleue settlement, which consisted of 26 mothers of infants who experienced stunting as cases and as many as 26 mothers of infants who did not experience stunting as controls (control). Data collection from February 27 to March 04 using a questionnaire through interviews. Data analysis using Chi-Square test SPSS program. The results of the study there was a relationship between energy and protein intake p = 0.003, there was a relationship between Low Birth Weight p = 0.005, there was a relationship between exclusive breastfeeding p = 0.012, there was a relationship between Early Breastfeeding Initiation p = 0.023, there was a relationship between history of infectious diseases p = 0.023 = 0.011, there is a relationship between family income p = 0.048 and there is a relationship between mother's knowledge p = 0.025 with stunting. Based on the research conducted, it can be concluded that the seven variables have a stunting relationship in the Indrajaya Public Health Center Work Area, Pidie Regency in 2022. It is expected that health workers can provide counseling regarding stunting prevention in children under two, such as providing adequate energy and protein intake.